Pengaruh Penambahan Ragi Tape dan Waktu Fermentasi Hasil Samping Cairan Pulpa terhadap Karakteristik Mutu Cuka Kakao (Theobroma cacao L.) - Awidyanata, Ida Bagus Gede; Ganda Putra, G.P; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 2 (2020): Juni, 2020)
The aim of this study was to determine the effect of adding ragi tape and the time of natural fermentation of the pulp byproducts of the fermented cocoa beans on the characteristics of the quality of cocoa vinegar and determining the addition of tape yeast and the natural fermentation time of the best pulp fluid for cocoa vinegar production. The experiments in this study used a randomized block design with two factors. The first factor is the addition of yeast tape consisting of 5 levels, namely without the addition of yeast tape (control), the addition of yeast tape 0.05% (w / v), 0.10% (w / v), 0.15% (w / v), 0.20% (w / v), the second factor is the fermentation time consisting of 6 levels, namely 5, 10, 15, 20, 25, 30 days. Treatment The addition of tape yeast has a very significant effect on acetic acid, pH, total dissolved solids, total sugar, has no significant effect on alcohol content in the fermented vinegar from the pulp fluid which is the by-product of cocoa bean fermentation. The length of fermentation treatment has a very significant effect on acetic acid, pH, total dissolved solids, total sugar, alcohol. The interaction between the two treatments had no significant effect on acetic acid, pH, total dissolved solids, alcohol content, and significant effect on total sugar in fermented cocoa vinegar products. The best treatment was obtained from the addition of 0.15% (w / v) yeast tape and 30 days fermentation time which produced cacao vinegar with acetic acid content of 2.40%, pH 3.37, total dissolved solids 4.25 o brix, total sugar 0.03%, and 0.00% alcohol. Keywords  : vinegar fermentasion, ragi tape, time of fermentation